A collagen‐coated PGA conduit for interpositional‐jump graft with end‐to‐side neurorrhaphy for treating facial nerve paralysis in rat. Issue 1 (8th January 2018) - Niimi, Yosuke; Matsumine, Hajime; Takeuchi, Yuichi; Hironobu, Osaki; Tsunoda, Satoshi; Miyata, Mariko; Yamato, Masayuki; Sakurai, Hiroyuki
Abstract : Purpose: This study investigated the potential of collagen‐coated polyglycolic acid (PGA) tube with interpositional jump graft (IPJG) in rat. Materials and Methods: A total of 16 Lewis rats were used in this study. Facial nerve paralysis was created by ligating facial nerve trunk with a ligature clip. The rats were divided into 3 groups. Nerve conduit group ( n  = 6) were treated by IPJG with collagen‐coated PGA tubes between the facial nerve trunks and the hypoglossal nerves. Autograft group ( n  = 6) were treated by IPJG with the greater auricular nerves. As the control group ( n  = 4), non‐treated‐model rats with facial nerve paralysis were used. The number of myelinated fibers, fiber diameter, axon diameter, myelin thickness, and g‐ratio, were analyzed histologically at 13 weeks after surgery. Compound muscle action potential (CMAP) and retrograde tracing were measured. Result: Although the number of myelinated fibers in autograft group (1957 ± 775) had significantly higher than that of nerve conduit group (90 ± 41, P  < .05), the nerve conduit group showed the regeneration of myelinated nerve axons. CMAP amplitude values of the autograft (4706 ± 1154 µV) and the nerve conduit groups (4119 ± 1397 µV) were significantly higher than that of the control group (915 ± 789 µV, P  < .05). Retrograde tracing confirmed the double innervation of mimetic muscles by the facial and hypoglossal nucleus in both groups. Conclusion: This study showed histologically and physiologically the superior effectiveness of performing IPJG with a collagen‐coated PGA conduit in a rat model.